PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP PENINGKATAN KETERAMPILAN BERPIKIR KRITIS : Model Pembelajaran, PBL, Berpikir Kritis - Riska Indah; Fifin Nabawiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is a literature review aimed at analyzing the effect of the Problem-Based Learning (PBL) model on improving students' critical thinking skills. PBL is a learning model that emphasizes contextual problem-solving as a means to develop higher-order thinking skills. The research method used was a literature review, reviewing various relevant previous research findings from national and international journals. The results of the literature synthesis indicate that the consistent application of the PBL model can improve students' critical thinking skills at various educational levels and fields of study. This is due to the characteristics of PBL, which requires students to analyze problems, seek information, propose hypotheses, and develop solutions independently and collaboratively. Thus, the PBL model has proven effective in developing students' critical thinking skills, creativity, and independent learning.